An Analysis of the Deli Serdang MUI's Opinion on the Support of a Husband of a Singer Who Dresses as a Woman - Barus, Agita Aidillah; Suparmin, Sudirman (DiH: Jurnal Ilmu Hukum, 2025)
This research aims to find out the facts and reasons/factors for providing support by husbands who work as singers who resemble women. Also to find out the Deli Serdang MUI's view of the legal status of alimony provided by husbands who work as singers in Patumbak District. In the context of income for family support, a Muslim needs to choose a job or business that does not conflict with religious principles. However, some husbands choose to do work that is involved in things that Allah hates. For one reason of economic livelihood, some men choose to imitate the appearance of women in the world of entertainment because they believe this will increase their appeal to audiences, especially in entertainment genres that emphasize visual appearance. Thus, it is important to know the legal status of the income generated from this work. The method used is empirical legal research with a qualitative approach. The primary data source is from an in-depth interview (Deep Interview) with the Indonesian Ulema Council (MUI Deli Serdang Regency) and her husband who works as a singer dressed as a woman to earn a living in Patumbak sub-district, Deli Serdang district. Research findings show that the factors that cause husbands to choose to work as singers who dress like women are economic reasons and the lack of work with sufficient salary to meet the family's needs. Legal Status: The livelihood provided by the process of obtaining it violates the law, so the results are haram. His work is haram and the results are haram, so the legal status of the income he provides to his family is haram, just like we give shopping to our parents' children and wives in an unlawful way.